2007
DOI: 10.1136/oem.2007.032482
|View full text |Cite
|
Sign up to set email alerts
|

New insight into solvent-related end-stage renal disease: occupations, products and types of solvents at risk

Abstract: Objectives:It has been shown that all-solvent exposure is associated with the progression of primary glomerulonephritis to end-stage renal disease (ESRD), but little is known about the type of solvents that are high risk. The aim of this study was to investigate the role of solvents by occupation, product and type.Methods:Using a retrospective cohort design, the authors studied 269 patients with non-end-stage and biopsy-proven primary glomerulonephritis diagnosed between 1994 and 2001 in Paris and its suburbs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“… ·There was a trend increasing HR with exposure duration before and its persistence after diagnosis. Jacob et al [ 13 ] (2007) retrospective cohort study 269 patients with non-ESRD and biopsy-proven primary GN a diagnosis between 1994 and 2001 in Paris and suburbs (including 167 IgAN patients) aggravation of IgAN to ESRD 2002–2004 269/167 ·This study showed the potential role of toluene and xylene, some petroleum products, ketones and possibly dichloromethane in the progression of GN a to ESRD. a GN, Glomerulonephritis; b RR, Relative Risk; c OR, Odds Ratio; d HR, Hazard Ratio; e (··), 95 % Confidence Interval …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“… ·There was a trend increasing HR with exposure duration before and its persistence after diagnosis. Jacob et al [ 13 ] (2007) retrospective cohort study 269 patients with non-ESRD and biopsy-proven primary GN a diagnosis between 1994 and 2001 in Paris and suburbs (including 167 IgAN patients) aggravation of IgAN to ESRD 2002–2004 269/167 ·This study showed the potential role of toluene and xylene, some petroleum products, ketones and possibly dichloromethane in the progression of GN a to ESRD. a GN, Glomerulonephritis; b RR, Relative Risk; c OR, Odds Ratio; d HR, Hazard Ratio; e (··), 95 % Confidence Interval …”
Section: Discussionmentioning
confidence: 93%
“…In a subsequent study, using data from the GN-PROGRESS cohort, Jacob et al [ 13 ] therefore systematically investigated the risk of progression to ESRD, by solvent-exposed job category, type of solvent-containing products, and by solvent or solvent family. In this analysis [ 13 ], they focused on the 269 patients with either IgAN or membranous nephropathy. Among solvents, the highest risks were found for: toluene/xylene (HR = 5.1, 95 CI 1.8–14.8), gasoline, fuel and gas-oil (HR = 8.6, 95 CI 2.7–27.4), and ketones (HR = 13.3, 95 % CI 1.4–123.5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional studies of workers chronically exposed to toluene and other organic solvents found an increased urinary albumin excretion compared to controls [ 50 ]. Among industrial solvents, toluene exposure was found to confer the greatest risk for progression to end-stage renal disease in patients with established glomerulonephritis [ 29 ]. Toluene has also been associated to direct induction of acute tubular necrosis and acute oliguric renal failure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%